Desigualdade e pobreza no Ceará: o caso do projeto São José - Araújo, Maria Helena de (2003)
The objective of this study was the analysis of the contribution of the São José Project in the reduction of the poverty and inequality in Ceará State, Northeast of Brazil. This Project started as a contract between the government of Ceará and the World Bank with the mainly goal of improving life conditions of the poor population in the rural zone of the state. The data analyzed, since April 1996 to June 2001, from reports, manuals, agreement of loan, statistics census, municipal development index, showed that the project reached 96% of the cities, that is, 177 among the 184 cities of Ceará State.In order to verify the changes in the social-economic aspects of the state, cities and communities, it were used tables and graphics with some social-economic indicators that allowed observing the effects of the different actions of the Project. It was identified that 78% of the subprojects were applied in the basic infrastructure, being 50% for rural electrification, mainly house electric power, 24% for water supply and 4% for other infrastructure activities. The productive subprojects represented 21% of the total, sprayed among several activities, from which 10% were applied to agricultural mechanization, mainly purchase of tractors, with doubtful impact on the soil structure. On the other side, the social area received only 1% of the total amount from subprojects. This analysis showed a contradictory reality: improvement of some life quality indicators, such as health, education, consumption, basic infrastructure (electrification and roads) and in other side, slowness in some taxes growth. In the area of education, it was observed a high level of adults illiteracy, associated to a low school time, mainly in the rural zone (1,9 years); as health concern, it was verified that still remains stroke of common diseases, among others. About basic sanitation, the sewerage system is precarious and attends only 20% of the population; the water supply is very low in comparison to the average of the northeastern region. The housing projects are not attending the demand of the necessity in the region, the roads an without conservation, and the unemployment index is hight. There is a high-income concentration, measured by Gini index, which is superior to the ones in the northeast region and Brazil. Between 1995 and 1999 this index decreased from 0.62 to 0.61. Although, it remained above the national and northeastern values, which are 0.59 and 0.60, respectively. The extension service does not have satisfactory quality and quantity to attend the needs of the region. This services and assistance are not offered equally to poor and riches, whites and blacks, men and women. In the rural zone the poverty is more serious. The indicators are below to the urban area, with exception to the unemployment. The per capita family income represents only 46% of the state average, and 22% of the national one, remained a high concentration of income and land. Finally, it can be said that the São José Project had a limited contribution to the municipal, state or regional profiles changing, despite of the enormous performance in the development of the electrification program in the rural zone. These results show that the electrification was not integrated with the others growth programs. Accurately, according to specific studies it is undeniable the relevance of the São José Project to the life standing improvement of the benefited public.